Synergism effect of Thiobacillus Thiooxidans and Thiobacillus Ferrooxidans on the bio-etching - Liu, Yu-de (2013)
The synergism effect of Thiobacillus ferrooxidans(T.f) and Thiobacillus thiooxidans(T.t) on bio-etching metal material was studied. The rates of bio-etching copper, tin bronze, T10, 40Cr were analysed and compared while T.f, T.t and the mixture of T.f and T.t was used separately. The maximal bio-etching rate of bio-etching above metals using the mixture of T.f and T.t is 3.4 times, 3.6 times, 2.5 times and 2.5 times than that of using T.f alone, respectively. The bio-etching effect of T.f can be enhanced by T.t mixed under the condition that Fe2+ ion and proper reductive sulphide exist, and the bio-etching rate is increased.